ALK4-SMAD2/3-SMAD4 signaling mediates the activin A-induced suppression of PTX3 in human granulosa-lutein cells. (1st August 2019) - Liu, Chang; Chang, Hsun-Ming; Yi, Yuyin; Fang, Ying; Zhao, Feiyan; Leung, Peter C.K.; Yang, Xiaokui
Abstract: As one of the members of the transforming growth factor-β (TGF-β) superfamily, activin A plays an important role in regulating follicular development and oocyte maturation. Pentraxin 3 (PTX3) is the key component that promotes the process of cumulus expansion during mammalian ovulation. At present, the regulation of PTX3 expression in human granulosa cells remains largely unknown. This study aimed to examine the effects of activin A on the expression of PTX3 in human granulosa-lutein (hGL) cells and to investigate the underlying molecular mechanisms. Using an established immortalized hGL cell line (SVOG) and primary hGL cells as study models, we demonstrated that activin A significantly increased the phosphorylation of SMAD2 and SMAD3, which suppressed the expression of PTX3 at both the mRNA and protein levels. Additionally, these effects induced by activin A were completely reversed by pretreatment with the TGF-β type I receptor inhibitor SB431542 and knockdown of ALK4. Furthermore, knockdown of SMAD2, SMAD3, or SMAD4 completely reversed the activin A-induced suppressive effects on PTX3 expression. Notably, the ChIP analyses demonstrated that phosphorylated SMADs could bind to human PTX3 promoter. Collectively, our results showed that the ALK4-SMAD2/3-SMAD4 signaling pathway most likely mediates the suppressive effect of activin A on PTX3 expression in hGL cells. Highlights: Activin A suppresses the expression of PTX3 in human granulosa-lutein cells. Type I receptor inhibitor SB431542 completely reverses activin-A-induced suppression of PTX3. Knockdown of SMAD2, SMAD3, or SMAD4 completely reverses activin A-induced suppression of PTX3. Activin A suppresses PTX3 expression via an ALK4-mediated SMAD-dependent pathway. SMAD3 binds to the PTX3 promoter.